The Role of IoT and AI in Advancing Wastewater Treatment Plant Efficiency - Tejasvi Arneja; Mayank Yadav (International Journal of Environmental Noise and Pollution Control, 2024)
Wastewater treatment facilities, or WWTPs, are essential for protecting the environment and human health because they clean wastewater before it is released into natural water bodies. The operational effectiveness and efficiency of WWTPs have undergone a significant transformation as a result of the integration of smart technology for real-time monitoring and control. This review looks at new developments in smart technologies that are being used in WWTPs, including data analytics, sensor networks, Internet of Things (IoT) devices, and automated control systems. This paper illustrates effective uses of these technologies through case studies and examples, highlighting their benefits, difficulties faced, and future possibilities for streamlining wastewater treatment procedures. The conversation emphasizes how important smart technologies are to the advancement of operational excellence and sustainability in wastewater treatment.
Keywords: Internet of Things; Sustainability; Wastewater treatment facilities; data analytics; sensor networks